Aerospace series. Connectors, electrical, circular bayonet coupling, ope rating temperature 175°C or 200°C continuous. Receptacle, hermetic, round flange, welding or brazing mounting. Product standard Part 007, (30th June 2015) - British Standards Institution
No abstract available